Carta de Roberto H. Todd a Horace M. Towner - Todd, Roberto H.; Towner, Horace M. (My University, 1922)
Conversación de Roberto H. Todd a Horace M. Towner.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Montgomery Reily, Emmet, 1866-1954; Towner, Horace Mann, 1855-1932; Partido Republicano (Puerto Rico); Gómez Brioso, José, 1855-1930; Barceló, Antonio R., 1868-1938; Partido Unión de Puerto Rico